A one-pot electrochemical synthesis of 2-aminothiazoles from active methylene ketones and thioureas mediated by NH4I - Yang, Shang-Feng; Li, Pei; Fang, Zi-Lin; Liang, Sen; Tian, Hong-Yu; Sun, Bao-Guo; Xu, Kun; Zeng, Cheng-Chu (Beilstein Journal of Organic Chemistry, 2022)
The electrochemical preparation of 2-aminothiazoles has been achieved by the reaction of active methylene ketones with thioureas assisted by ᴅʟ-alanine using NH4I as a redox mediator. The electrochemical protocol proceeds in an undivided cell equipped with graphite plate electrodes under constant current conditions. Various active methylene ketones, including β-keto ester, β-keto amide, β-keto nitrile, β-keto sulfone and 1,3-diketones, can be converted to the corresponding 2-aminothiazoles. Mechanistically, the in situ generated α-iodoketone was proposed to be the key active species.
Keywords: 2-aminothiazoles; electrosynthesis; indirect electrolysis; halide ion

(untitled) - de Souza, M. V. N. (J. Sulfur Chem., 2005)

(untitled) - Samadhiya, P.; Sharma, R.; Srivastava, S. K.; Srivastava, S. D. (J. Serb. Chem. Soc., 2012)

(untitled) - Sarıgüney, A. B.; Kocabaş, E.; Erci, F.; Torlak, E.; Coşkun, A. (J. Heterocycl. Chem., 2018)

(untitled) - Jeong, K.-w.; Lee, J.-h.; Park, S.-m.; Choi, J.-H.; Jeong, D.-Y.; Choi, D.-H.; Nam, Y.; Park, J.-H.; Lee, K.-N.; Kim, S.-M.; Ku, J.-M. (Eur. J. Med. Chem., 2015)

(untitled) - Hutchinson, I.; Jennings, S. A.; Vishnuvajjala, B. R.; Westwell, A. D.; Stevens, M. F. G. (J. Med. Chem., 2002)

(untitled) - Ottmann, O.; Saglio, G.; Apperley, J. F.; Arthur, C.; Bullorsky, E.; Charbonnier, A.; Dipersio, J. F.; Kantarjian, H.; Khoury, H. J.; Kim, D.-W.; Healey, D.; Strauss, L.; et al. (Blood Cancer J., 2018)

(untitled) - Kalkhambkar, R. G.; Kulkarni, G. M.; Shivkumar, H.; Rao, R. N. (Eur. J. Med. Chem., 2007)

(untitled) - Singh, N.; Bhati, S. K.; Kumar, A. (Eur. J. Med. Chem., 2008)

(untitled) - Kaupp, G.; Amer, F. A.; Metwally, M. A.; Abdel-Latif, E. (J. Heterocycl. Chem., 2003)

(untitled) - Alajarín, M.; Cabrera, J.; Pastor, A.; Sánchez-Andrada, P.; Bautista, D. (J. Org. Chem., 2006)

(untitled) - Liu, Y.; Chen, H.; Yin, D.; Sun, B. (Molecules, 2010)

(untitled) - Al-Dujaili, A. H.; Atto, A. T.; Al-Kurde, A. M. (Eur. Polym. J., 2001)

(untitled) - Abu-Melha, S. (Pigm. Resin Technol., 2019)

(untitled) - Kashyap, S. J.; Garg, V. K.; Sharma, P. K.; Kumar, N.; Dudhe, R.; Gupta, J. K. (Med. Chem. Res., 2012)

(untitled) - Das, D.; Sikdar, P.; Bairagi, M. (Eur. J. Med. Chem., 2016)

(untitled) - Gümüş, M.; Yakan, M.; Koca, İ. (Future Med. Chem., 2019)

(untitled) - Jadhav, P. M.; Kantevari, S.; Tekale, A. B.; Bhosale, S. V.; Pawar, R. P.; Tekale, S. U. (Phosphorus, Sulfur Silicon Relat. Elem., 2021)

(untitled) - Hantzsch, A.; Weber, J. H. (Ber. Dtsch. Chem. Ges., 1887)

(untitled) - Zav'yalov, S. I.; Kravchenko, N. E.; Ezhova, G. I.; Kulikova, L. B.; Zavozin, A. G.; Dorofeeva, O. V. (Pharm. Chem. J., 2007)

(untitled) - Dziuk, B.; Kyzioł, J. B.; Zaleski, J.; Ejsmont, K.; Zarychta, B. (J. Heterocycl. Chem., 2018)

(untitled) - Abedi-Jazini, Z.; Safari, J.; Zarnegar, Z.; Sadeghi, M. (Polycyclic Aromat. Compd., 2018)

(untitled) - Safari, J.; Shokrani, Z.; Zarnegar, Z. (Polycyclic Aromat. Compd., 2020)

(untitled) - Narender, M.; Reddy, M. S.; Kumar, V. P.; Srinivas, B.; Sridhar, R.; Nageswar, Y. V. D.; Rao, K. R. (Synthesis, 2007)

(untitled) - Meng, G.; Wang, M.; Zheng, A.; Dou, J.; Guo, Z. (Green Chem. Lett. Rev., 2014)

(untitled) - Kuarm, B. S.; Madhav, J. V.; Rajitha, B. (Lett. Org. Chem., 2011)

(untitled) - de Andrade, V. S. C.; de Mattos, M. C. S. (Synthesis, 2018)

(untitled) - Sadeghi, M.; Safari, J.; Zarnegar, Z. (RSC Adv., 2016)

(untitled) - Zarnegar, Z.; Sadeghi, M.; Alizadeh, R.; Safai, J. (J. Mol. Liq., 2018)

(untitled) - Sun, J.; Ge, H.; Zhen, X.; An, X.; Zhang, G.; Zhang-Negrerie, D.; Du, Y.; Zhao, K. (Tetrahedron, 2018)

(untitled) - Frontana-Uribe, B. A.; Little, R. D.; Ibanez, J. G.; Palma, A.; Vasquez-Medrano, R. (Green Chem., 2010)

(untitled) - Francke, R. (Beilstein J. Org. Chem., 2014)

(untitled) - Yan, M.; Kawamata, Y.; Baran, P. S. (Chem. Rev., 2017)

(untitled) - Jiang, Y.; Xu, K.; Zeng, C. (Chem. Rev., 2018)

(untitled) - Liang, S.; Zeng, C.-C. (Curr. Opin. Electrochem., 2020)

(untitled) - Novaes, L. F. T.; Liu, J.; Shen, Y.; Lu, L.; Meinhardt, J. M.; Lin, S. (Chem. Soc. Rev., 2021)

(untitled) - Wang, Z.-Q.; Meng, X.-J.; Li, Q.-Y.; Tang, H.-T.; Wang, H.-S.; Pan, Y.-M. (Adv. Synth. Catal., 2018)

(untitled) - Li, J.-S.; Xie, X.-Y.; Yang, P.-P.; Jiang, S.; Tao, L.; Li, Z.-W.; Lu, C.-H.; Liu, W.-D. (Adv. Synth. Catal., 2020)

(untitled) - Ahdenov, R.; Mohammadi, A. A.; Makarem, S.; Taheri, S.; Mollabagher, H. (Heterocycl. Commun., 2022)

(untitled) - Liang, S.; Zeng, C.-C.; Tian, H.-Y.; Sun, B.-G.; Luo, X.-G.; Ren, F.-z. (J. Org. Chem., 2016)

(untitled) - Liang, S.; Zeng, C.-C.; Tian, H.-Y.; Sun, B.-G.; Luo, X.-G.; Ren, F.-z. (Adv. Synth. Catal., 2018)

(untitled) - Liang, S.; Xu, K.; Zeng, C.-C.; Tian, H.-Y.; Sun, B.-G. (Adv. Synth. Catal., 2018)

(untitled) - Li, P.; Yang, S.-F.; Fang, Z.-L.; Cui, H.-R.; Liang, S.; Tian, H.-Y.; Sun, B.-G.; Zeng, C.-C. (J. Environ. Chem. Eng., 2022)

(untitled) - Shaikh, I. R. (J. Catal., 2014)

(untitled) - Safari, J.; Shokrani, Z.; Zarnegar, Z. (Polycyclic Aromat. Compd., 2020)